Antibiotic therapy for acute uncomplicated appendicitis: a systematic review and meta-analysis - Prechal, Daniela Carolin; Damirov, Fuad; Grilli, Maurizio (International journal of colorectal disease, 2019)
PurposeAppendectomy has been the gold standard for every form of appendicitis. In recent years, though, it has repeatedly been claimed that for acute uncomplicated appendicitis, antibiotic therapy can be an equivalent treatment. The aim of this meta-analysis was to determine if antibiotic therapy is a safe and effective alternative to appendectomy for acute uncomplicated appendicitis.MethodsIn a systematic literature review, relevant databases were searched for randomized studies comparing appendectomy with antibiotic treatment for uncomplicated acute appendicitis. Two independent reviewers performed study selection and data extraction. The primary endpoint was the successful treatment of appendicitis. Secondary endpoints were pain intensity, duration of hospitalization, absence from work, and the incidence of complications.ResultsFive randomized controlled studies (n = 1430 patients) fulfilled the inclusion criteria. Of the 727 patients treated initially with antibiotics, 272 (37.4%) underwent secondary appendectomy within 1 year (treatment effectiveness: 62.6% compared to 96.3% in the surgical group, RR 0.65, 95% CI 0.55-0.76, p < 0.00001). Neither duration of hospital stay (MD 0.11 days, 95% CI: − 0.22-0.43, p = 0.53) nor the probability of complication-free treatment (RR 1.08, 95% CI: 0.97-1.22, p = 0.16) were significantly different between the two treatments. Absence from work was significantly shorter in the antibiotic group (MD − 2.49 days, 95% CI: − 4.59-− 0.40, p = 0.02).ConclusionsThis meta-analysis shows that appendectomy is more effective than antibiotic therapy for definitive cure of acute uncomplicated appendicitis. However, since the incidence of complications does not differ between the two treatments, antibiotic therapy might be a reasonable alternative for selected patients.
Gesehen am 30.09.2019